Identity Theories: from decentering to “self-invention” - Zarta Rojas, Fabian Andrey (Revista Colombiana de Ciencias Sociales, 2025)
In this reflection article we have attempted to explore the advance of sociological theories based on the concept of identity as a reflection and “invention of the self,” integrating and clarifying, little by little, the subjectcontext dialectic through Bourdieu’s approaches. and Kauffman, without attempting to cover all human and social disciplines. The text is developed in the following points: the ambiguity of the concept of identity; from the decentering of the subject to the “invention of oneself” and finally, the Ego and the “invention of oneself”: from reflection to reflection. An initial conclusion is reached in which identity ends up being a subjective representation, a fact that occurs due to the entry of man into the community; Thus, today, at the beginning of the 21st century, what is at stake is no longer a project but a construction of identity throughout life and the request for reflection, analysis and decision-making about oneself and about the context.